Real-world correlation between therapeutic drug monitoring and clinical outcomes of the antifungal drug posaconazole: a single-center retrospective cohort study - Yi, Qiaoyan; Dong, Lin; Wang, Peng; Shi, Yinping; Yang, Yilei; Dong, Zhonghua; Li, Siwen; Li, Yan; Huang, Xin; Liu, Jinjuan; Shi, Haiyan; Wang, Hongmei (Frontiers in Pharmacology, 2025)
ObjectivePosaconazole is a first-line drug for preventing invasive fungal disease (IFD) in patients undergoing haematopoietic stem cell transplantation (HSCT). Few retrospective studies have examined the impact of therapeutic drug monitoring (TDM) on preventing IFD with posaconazole. This study was designed to evaluate the efficacy, safety, and cost-effectiveness of posaconazole in preventing IFD based on real-world data.MethodsThis single-centre, retrospective cohort study analyzed the use of posaconazole for fungal prophylaxis in HSCT patients at the First Affiliated Hospital of Shandong First Medical University (Shandong Provincial Qianfoshan Hospital). Patients were classified into TDM and non-TDM groups based on their TDM status. Clinical data were analyzed using propensity score matching (PSM) to further elucidate the role of TDM in posaconazole prophylaxis.ResultsAfter PSM, the prophylactic success rate was significantly higher in the TDM group (100%) than in the non-TDM group (52.9%) (P = 0.003). There was no statistically significant difference in gastrointestinal, hepatic and renal adverse effects between the two groups (P > 0.05). Both the total cost of treatment and the cost of medication were lower in the TDM group compared to the non-TDM group.ConclusionReal-world data demonstrate that TDM enhances the effectiveness of posaconazole in preventing IFD in HSCT patients and moderately reduces treatment costs.